Functional Connectivity in Chronic Schizophrenia: An EEG Resting-State Study with Corrected Imaginary Phase-Locking - Domingos, Christophe; Więcławski, Wiktor; Frycz, Sandra; Wojcik, Maja; Jáni, Martin; Dudzińska, Olga; Adamczyk, Przemysław; Ros, Tomas (Brain and behavior, 2025)
UNLABELLED: Schizophrenia is a complex disorder characterized by altered brain functional connectivity, detectable during both task and resting state conditions using different neuroimaging methods. To this day, electroencephalography (EEG) studies have reported inconsistent results, showing both hyper- and hypo-connectivity with diverse topographical distributions. Interpretation of these findings is complicated by volume-conduction effects, where local brain activity fluctuations project simultaneously to distant scalp regions (zero-phase lag), inducing spurious inter-electrode correlations. AIM: In the present study, we explored the network dynamics of schizophrenia using a novel functional connectivity metric-corrected imaginary phase locking value (ciPLV)-which is insensitive to changes in amplitude as well as interactions at zero-phase lag. This method, which is less prone to volume conduction effects, provides a more reliable estimate of sensor-space functional network connectivity in schizophrenia. METHODS: We employed a cross-sectional design, utilizing resting state EEG recordings from two adult groups: individuals diagnosed with chronic schizophrenia (n = 30) and a control group of healthy participants (n = 30), all aged between 18 and 55 years old. RESULTS: Our observations revealed that schizophrenia is characterized by a prevalence of excess theta (4-8 Hz) power localized to centroparietal electrodes. This was accompanied by significant alterations in inter- and intra-hemispheric functional network connectivity patterns, mainly between frontotemporal regions within the theta band and frontoparietal regions within beta/gamma bands. CONCLUSIONS: Our findings suggest that patients with schizophrenia demonstrate long-range electrophysiological connectivity abnormalities that are independent of spectral power (i.e., volume conduction). Overall, distinct hemispheric differences were present in frontotemporo-parietal networks in theta and beta/gamma bands. While preliminary, these alterations could be promising new candidate biomarkers of chronic schizophrenia.
Keywords: EEG; Rest; mozek; Humans; lidé středního věku; mapování mozku; Nerve Net; Chronic Disease; schizofrenie; Female; mladý dospělý; dospělí; power spectrum; resting‐state; lidé; elektroencefalografie; Schizophrenia; schizophrenia; Brain Mapping; Adult; nervové dráhy; ženské pohlaví; phase locking value; Neural Pathways; Male; Middle Aged; chronická nemoc; Brain; Adolescent; odpočinek; Cross-Sectional Studies; Young Adult; Electroencephalography; functional connectivity; nervová síť; mužské pohlaví; průřezové studie; mladiství